Learn Math Questions

from a handpicked tutor in LIVE 1-to-1 classes

from a handpicked tutor in LIVE 1-to-1 classes

# Using the completing-the-square method, rewrite f(x) = x^{2} + 4x - 1 in vertex form.

**Solution:**

The vertex form of the equation is given by

f(x) = a(x - h)^{2 }+ k

Given, f(x) = x^{2} + 4x - 1

Converting to vertex form,

x^{2} - 6x + 2 = x^{2} + 4x + 4 - 4 - 1

f(x) + 4 = (x + 2)^{2} - 1

f(x) = (x + 2)^{2} - 4 - 1

f(x) = (x + 2)^{2} - 5

Therefore, the equation in vertex form is f(x) = (x + 2)^{2 }- 5.

## Using the completing-the-square method, rewrite f(x) = x^{2} + 4x - 1 in vertex form.

**Summary:**

Using the completing the square method, the equation f(x) = x^{2} + 4x - 1 in vertex form is f(x) = (x + 2)^{2 }- 5.

Math worksheets and

visual curriculum

visual curriculum